(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2025)
Abstract This manuscript discusses the talent management practices applied by productions in drama or film. The study encompasses two main objectives: firstly, to understand how actors embody and internalize the roles of Persons with Disabilities (PWD), and secondly, to identify the duration actors require to fully comprehend and internalize PWD roles assigned to them. Findings from the study indicate that the embodiment of PWD characters can be achieved through observational studies of actual individuals with disabilities, imitation of characteristics, strategic casting, as well as thoughtful expression and appreciation of the given roles. The research participants each required between two to eight weeks to completely internalize their respective roles. This research contributes strategic insights beneficial to emerging production companies, providing methodologies that facilitate the cultivation of versatile actors who can convincingly portray a diverse range of characters through structured teaching and training processes offered by production entities. Effective talent management is crucial for the success of dramas and films. A well-crafted and sincere production can attract and maintain audience support, thereby advancing the local film industry’s initiatives. Abstrak Naskhah ini membincangkan tentang pengurusan bakat yang diterapkan oleh sesebuah produksi ke dalam layar drama mahupun filem. Kajian ini mempunyai dua objektif, iaitu memahami cara penjiwaan watak OKU yang dibawa oleh pelakon, dan mengenalpasti jangka masa yang diambil oleh pelakon untuk menghayati dan mendalam watak OKU yang diberikan. Melalui kajian, watak OKU dapat dijiwai melalui pemerhatian terhadap individu OKU, peniruan gaya, pemilihan pelakon dalam sesebuah naskhah, dan pengkspresian dan aprisiasi watak dengan baik. Informan kajian masing-masing mengambil masa selama dua hingga lapan minggu untuk menghayati watak sepenuhnya. Penyelidikan ini menyumbang kepada daya pemikiran yang strategik kepada syarikat produksi lain yang sedang menapak sekali gus naskhah ini untuk melahirkan pelakon yang serba boleh dan mampu melakonkan apa-apa sahaja watak yang diberi melalui proses pengajaran dan latihan yang disediakan oleh pihak produksi. Pengurusan bakat penting untuk kejayaan drama dan filem. Melalui karya yang dibuat dengan baik dan jujur, ia dapat meyakinkan penonton untuk terus menyokong usaha industri perfileman tanah air.